Test-Retest Reliability of Saccadic Measures in Subjects at Risk for Huntington Disease - Blekher, Tanya; Weaver, Marjorie R; Cai, Xueya; Hui, Siu; Marshall, Jeanine; Jackson, Jacqueline Gray; Wojcieszek, Joanne; Yee, Robert D; Foroud, Tatiana M (Investigative ophthalmology & visual science, 2009)
Abnormalities in saccades appear to be sensitive and specific biomarkers in the prediagnostic stages of Huntington disease (HD). The goal of this study was to evaluate test-retest reliability of saccadic measures in prediagnostic carriers of the HD gene expansion (PDHD) and normal controls (NC). The study sample included 9 PDHD and 12 NC who completed two study visits within an approximate 1-month interval. At the first visit, all participants completed a uniform clinical evaluation. A high-resolution, video-based system was used to record eye movements during completion of a battery of visually guided, antisaccade, and memory-guided tasks. Latency, velocity, gain, and percentage of errors were quantified. Test-retest reliability was estimated by calculating the intraclass correlation (ICC) of the saccade measures collected at the first and second visits. In addition, an equality test based on Fisher's z-transformation was used to evaluate the effects of group (PDHD and NC) and the subject's sex on ICC. The percentage of errors showed moderate to high reliability in the antisaccade and memory-guided tasks (ICC = 0.64-0.93). The latency of the saccades also demonstrated moderate to high reliability (ICC = 0.55-0.87) across all tasks. The velocity and gain of the saccades showed moderate reliability. The ICC was similar in the PDHD and NC groups. There was no significant effect of sex on the ICC. Good reliability of saccadic latency and percentage of errors in both antisaccade and memory-guided tasks suggests that these measures could serve as biomarkers to evaluate progression in HD.